Quadruple‐Resonance Magic‐Angle Spinning NMR Spectroscopy of Deuterated Solid Proteins1. Issue 9 (29th January 2014) - Akbey, Ümit; Nieuwkoop, Andrew J.; Wegner, Sebastian; Voreck, Anja; Kunert, Britta; Bandara, Priyanga; Engelke, Frank; Nielsen, Niels Chr.; Oschkinat, Hartmut
Abstract 1H‐detected magic‐angle spinning NMR experiments facilitate structural biology of solid proteins, which requires using deuterated proteins. However, often amide protons cannot be back‐exchanged sufficiently, because of a possible lack of solvent exposure. For such systems, using 2H excitation instead of 1H excitation can be beneficial because of the larger abundance and shorter longitudinal relaxation time, T1, of deuterium. A new structure determination approach, "quadruple‐resonance NMR spectroscopy", is presented which relies on an efficient 2H‐excitation and 2H‐13C cross‐polarization (CP) step, combined with 1H detection. We show that by using 2H‐excited experiments better sensitivity is possible on an SH3 sample recrystallized from 30 % H2O. For a membrane protein, the ABC transporter ArtMP in native lipid bilayers, different sets of signals can be observed from different initial polarization pathways, which can be evaluated further to extract structural properties.